ENHANCING SCHOOL SAFETY AND SECURITY: DEVELOPING AND IMPLEMENTING EFFECTIVE PROTOCOLS FOR A SECURED LEARNING ENVIRONMENT - Osegbue, Gloria Chineze; Ohamobi, Ifunanya Nkechi; Alordiah, Caroline Ochuko (African Journal of Social and Behavioural Sciences, 2025)
School safety and security have become pressing concerns due to the increasing incidents of violence, bullying, and external threats that disrupt learning environments. This study explores developing and implementing structured school safety and security protocols, emphasising key threats such as student violence, vandalism, armed intrusions, and natural disasters. It discusses essential components of an effective safety framework, including risk assessment, physical security measures, emergency preparedness, and behavioural policies. The study also highlights challenges such as financial constraints, resistance to change, ethical concerns, and policy inconsistencies that hinder effective implementation. Best practices from successful school safety programs are examined, with recommendations for strengthening legislation, increasing funding, and integrating technology-driven security solutions. The study concludes that ensuring school safety requires a multi-stakeholder approach involving policymakers, educators, parents, and law enforcement agencies. Continuous monitoring and adaptation of safety protocols are essential for maintaining a secure and conducive learning environment.